Mathematical Problem Solving Abilities Viewed by Intelligence Quotient and Gender Grade 5th - Alifani, Shabrina Mei; Suyitno, Hardi; Supriyadi, Supriyadi (Journal of Primary Education, 2018)
Problem solving is part of a very important mathematical curriculum. Through this aspect of mathematical ability such as the application of rules on non-routine issues, pattern discoveries, etc. can be developed better. The purpose of this research are: (1) to analyze mathematical problem solving ability viewed by IQ; (2) to analyze the mathematical problem solving ability viewed by gender. This type of research is qualitative. Research subjects consisted of 6 students VB grade SD Nusaputera Semarang 2016 school year. Qualitative analysis includes data reduction, display data, and conclusion drawing. The results of this study are (1) there are three categories of IQ that is high average, average, and low average, which has the ability to solve the best math problem that are high average, then average, and the last is low categories which refers to their ability to solve mathematical problem solving; (2) based on the total number of indicators that can be fulfilled by male gender and female' gender in this study, it shows that female's mathematics problem solving ability is better than that of male. Important finding of this research is that IQ and gender determine the level of problem solving ability of math student. This research can be used as a guide in giving learning to students in improving problem solving ability of math based on IQ and gender difference.